DKA with Severe Hypertriglyceridemia and Cerebral Edema in an Adolescent Boy: A Case Study and Review of the Literature. (20th January 2016) - Saengkaew, Tansit; Sahakitrungruang, Taninee; Wacharasindhu, Suttipong; Supornsilchai, Vichit
Abstract : A 13-year-old adolescent boy with type 1 diabetes mellitus (1b) presented with diabetic ketoacidosis (DKA) and cerebral edema. Grossly lipemic serum and lipemia retinals due to extremely high triglyceride (TG) level were observed without evidence of xanthoma or xanthelasma. Cerebral edema was treated by appropriate ventilation and mannitol administration. Normal saline was carefully given and regular insulin was titrated according to blood sugar levels. Triglyceride levels were reduced from 9, 800 mg/dL to normal range within 9 days after conventional treatment was commenced without antilipid medication. Based on our review of the literature, this is the first reported case of confirmed pediatric DKA with severe hypertriglyceridemia and cerebral edema. In patients with DKA and hypertriglyceridemia, clinicians should be mindful of the possibility of associated acute pancreatitis and cerebral edema.